CONCEPTUALIZATION OF THE WORLD AND LINGUISTIC MEANS OF ITS EXPRESSION IN THE KINDRED LANGUAGES - Lazarovich, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Linguistic means and ways of the conceptualization of the world in the Ukrainian and Polish languages are studied in the article. Common and different features in the conceptspheres of two kindred languages are described on the example of the analysis of separate fragments of the language picture of the world.